2015
DOI: 10.1371/journal.pone.0138854
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Method for Transportation of Mouse Embryos Using Microtubes and a Warm Box

Abstract: Generally, transportation of preimplantation embryos without freezing requires incubators that can maintain an optimal culture environment with a suitable gas phase, temperature, and humidity. Such incubators are expensive to transport. We reported previously that normal offspring were obtained when the gas phase and temperature could be maintained during transportation. However, that system used plastic dishes for embryo culture and is unsuitable for long-distance transport of live embryos. Here, we developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Thus, researchers may consider practicing the sterile technique strictly and selecting culture instruments carefully. Washing the instruments with the culture medium immediately before use is recommended in some special cases 151, 152, 153…”
Section: Current Issues With Culture Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, researchers may consider practicing the sterile technique strictly and selecting culture instruments carefully. Washing the instruments with the culture medium immediately before use is recommended in some special cases 151, 152, 153…”
Section: Current Issues With Culture Mediamentioning
confidence: 99%
“…An analysis of the concentration by using at least a three-level screening design is necessary to understand such responses with the culture medium immediately before use is recommended in some special cases. [151][152][153] Then, the optimal concentration of component B is determined at the optimal concentration of component A. This strategy, which usually has been used, has a big disadvantage of missing the optimal point because there are some unexamined areas in the range of parameters.…”
Section: Contamination Of a Mediummentioning
confidence: 99%
“…Mammalian preimplantation embryos have been cultured in various devices, including flasks, fluidic devices, glass tubes, and handmade devices [22][23][24][25] . However, it has been challenging to determine the optimal device for live-cell imaging because these devices cannot be reliably and safely sealed, nor can embryos be easily observed through all devices.…”
Section: Discussionmentioning
confidence: 99%
“…The thermal bottle is inherently mobile and readily available for purchase and has a high heat-retaining property. In our experiments, we used a 500-μL microtube [ 13 ] as a sealed tube instead of a 5-mL plastic tube because a microtube requires a minimal volume of medium to culture embryos. The water temperature in the thermal bottle was measured every 10 min for up to 2 days using a Super Thermochron temperature logger (1922T, KN Laboratories, Osaka, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…In that study, mouse embryos were transferred to a microtube, which was usually used for molecular analysis, and the tubes were transferred into a plastic bag containing a mixed gas (5% CO 2 , 5% O 2 ). We found that this method enabled the culture of good-quality embryos and also allowed the shipment of live embryos by parcel delivery [ 13 ]. However, because this warm box is not commercially available; its adoption has not yet spread to other laboratories.…”
Section: Introductionmentioning
confidence: 99%